Optimizing a Fed-Batch High-Density Fermentation Process for Medium Chain-Length Poly(3-Hydroxyalkanoates) in Escherichia coli - Scheel, Ryan A.; Ho, Truong; Kageyama, Yuki; Masisak, Jessica; McKenney, Seamus; Lundgren, Benjamin R.; Nomura, Christopher T. (Frontiers in Bioengineering and Biotechnology, 2021)
Production of medium chain-length (MCL) poly(3-hydroxyalkanoates) [PHA] polymers with tightly defined compositions is an important area of research to expand the application and improve the properties of these promising biobased and biodegradable materials. PHA polymers with homopolymeric or defined compositions exhibit attractive material properties such as increased flexibility and elasticity relative to poly(3-hydroxybutyrate) [PHB]; however, these polymers are difficult to biosynthesize in native PHA-producing organisms, and there is a paucity of research towards developing high-density cultivation methods while retaining compositional control. In this study, we developed and optimized a fed-batch fermentation process in a stirred tank reactor, beginning with the biosynthesis of poly(3-hydroxydecanoate) [PHD] from decanoic acid by β-oxidation deficient recombinant E. coli LSBJ using glucose as a co-substrate solely for growth. Bacteria were cultured in two stages, a biomass accumulation stage (37 °C, pH 7.0) with glucose as the primary carbon source and a PHA biosynthesis stage (30 °C, pH 8.0) with co-feeding of glucose and a fatty acid. Through iterative optimizations of semi-defined media composition and glucose feed rate, 6.0 g of decanoic acid was converted to PHD with an 87.5% molar yield (4.54 g L-1). Stepwise increases in the amount of decanoic acid fed during the fermentation correlated with an increase in PHD, resulting in a final decanoic acid feed of 25 g converted to PHD at a yield of 89.4% (20.1 g L-1, 0.42 g L-1 h-1), at which point foaming became uncontrollable. Hexanoic acid, octanoic acid, 10-undecenoic acid, and 10-bromodecanoic acid were all individually supplemented at 20 g each and successfully polymerized with yields ranging from 66.8 to 99.0% (9.24 to 18.2 g L-1). Using this bioreactor strategy, co-fatty acid feeds of octanoic acid/decanoic acid and octanoic acid/10-azidodecanoic acid (8:2 mol ratio each) resulted in the production of their respective copolymers at nearly the same ratio and at high yield, demonstrating that these methods can be used to control PHA copolymer composition.